Psychological Resilience of Tulungagung Marble Artisans in Facing Legal Challenges and Market Competition - Purborini, Vivi Sylvia; Masela, Minggus S.; Prahoro, Alfedro Putut; Sari, Lilis Yunita; Putri, Aisyah Bella Cahya (Rechtsvinding, 2025)
This study analyzes the psychological resilience of marble artisans in Tulungagung in facing increasingly complex legal challenges and market competition. The local marble industry confronts complicated licensing and environmental regulations, low levels of legal literacy, and competitive pressure from imported products and shifting consumer preferences, all of which generate psychological burdens such as stress and anxiety for the artisans. The research employs a qualitative approach enriched with quantitative data, using in-depth interviews with 18 artisans, field observations in marble production centers, and a resilience questionnaire administered to 20 respondents with an instrument adapted from the 25-item Connor-Davidson Resilience Scale.​ The results show an average resilience score of 72.8 (medium–high category), with optimism and persistence as the strongest dimensions, while stress regulation remains relatively weak, particularly in relation to legal and economic pressures. Thematic analysis reveals three main themes: the meaning of work as cultural heritage and social identity, legal uncertainty as a source of psychological stress, and community adaptation through mutual support and marketing innovation, including simple use of digital media. The findings also indicate a positive correlation between psychological resilience and market adaptation capacity, where artisans with higher resilience tend to be more innovative and more willing to experiment with new business strategies. The study concludes that resilience functions as important psychological capital for business sustainability, but its effectiveness is constrained by low legal awareness, thereby necessitating integrated interventions in the form of legal literacy empowerment and community-based resilience training for marble artisans in Tulungagung